Oral rehabilitation of a 21-month-old patient: clinical case report - Gonzales-Llompart , Mayra (2024)
Currently there are pediatric patients with early childhood caries including severe and fast affectation of primary teeth, with possible pulpares injuries and infectious complications that determine the premature loss of some teeth. The specialty of pediatric dentistry offers a number of restorative and rehabilitation treatment that allows the restoration of aesthetics, phonetics, mastication and occlusion necessary for the proper normal physiological and emotional development. The purpose of this paper is to report the oral restorative and rehabilitation treatment performed in a female patient 1 year 9 months old, with different unfavorable during treatment, such as denial of the treatment plan presented to parents factors. Direct and indirect pulp capping is performed in the upper anterior parts, restorations modified ionomer resin and acetate placing crowns on the 4 top incisors glass. The results are the eradication of pain in the anterior region, restoring aesthetics, phonetics, mastication, occlusion and eradicate previous negative experiences with the dentist parents and child. Oral rehabilitation of children in primary teeth allows smooth transition between primary and permanent dentition.